Touching body, soul, and spirit? Understanding external applications from integrative medicine: A mixed methods systematic review - Mühlenpfordt, Inga; Blakeslee, Sarah B.; Everding, Janina; Cramer, Holger; Seifert, Georg; Stritter, Wiebke (Frontiers in Medicine, 2022)
Introduction External applications from anthroposophic medicine (EAAM) are touch-based applications such as rhythmical massages, embrocations, and compresses that serve as components of complementary treatment concepts for various diseases. The aim of this review is to gain an understanding of typical indications and outcomes and to systematically assess the effectiveness and safety of EAAM. Materials and methods Medline/PubMed, CINAHL, the Cochrane Library, Embase, and PsycINFO were searched through May 2021 and supplemented by searches in specialized databases and personal requests to experts in the field. Studies and case reports on EAAM in patients, as well as healthy individuals, were included in the qualitative synthesis. Outcome parameters depending on each study were grouped as effect themes and assigned to study clusters using Thematic Analysis for a thematic overview of effect patterns. Results Four RCTs, 7 cohort studies, 1 mixed-methods, 1 retrospective, 4 qualitative studies, 3 case series, and 25 case reports on EAAM were identified. The analysis indicated various effects of EAAM on physiological as well as psychological health indicators and patterns of effect development. Study quality was found to be high for only 2 studies, and moderate for 1 study, and all remaining 45 studies showed a moderate or high risk of bias or were not ratable with used rating tools. Conclusion The included studies present a wide range of potential indications for EAAM, while showing methodological drawbacks. To determine whether EAAM can be considered an effective treatment option, clinical studies exploring the effect of different EAAM modalities on defined patient groups are recommended for the future. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=214030], identifier [CRD42020214030].